THE USE OF CULTURAL AND ENVIRONMENTAL HERITAGE IN EDUCATIONAL CONTEXTS BETWEEN SPACES, IDENTITIES, ATTITUDES, AND COGNITIVE WELL-BEING - Nuzzaci, Antonella (International Journal of Research -GRANTHAALAYAH, 2024)
The paper explores some links between educational research, the use of cultural and environmental heritage and education, where it is possible to combine knowledge, disciplines, and skills to strengthen the cultural profile of the school population, but also to bring about important changes in attitudes and behavior. The world’s cultural and environmental heritage, which collects the traces of extraordinary but also tragic events in human history, can act as a unifying force for peaceful coexistence for the whole of humanity, enabling future citizens to participate in democratic debate and make informed choices about the social challenges they face. It therefore contributes not only to the development of knowledge, but also to the ability of children, young people, and adults to understand contemporary problems by placing them in human, social, environmental, historical, and cultural contexts that help them to live. For cultural heritage to contribute to the recovery of knowledge, researchers, teachers, and operators must be able to share a solid research background that allows them to address the various issues relating to the quality of the experiences of use carried out in school contexts, with the aim of improving the learning processes of users. In fact, the cultural and environmental resources of the territory can only be a real methodological resource for improving cognitive well-being and the overall quality of education at all levels if they are seen as useful tools for different types of learning (cognitive, social, etc.) and not as general educational tools. The paper therefore questions the use of cultural and environmental heritage in education and its adequacy with respect to learning conditions, pausing to consider also the role played by attitudes to fruition, highlighting those elements and dimensions that can contribute to redefining the relationship between education, goods, and environment, in the idea of strengthening interpretative repertoires in educational contexts.